The importance of interest rates for forecasting the exchange rate - Hilde C. Bjørnland; Håvard Hungnes (Statistics Norway, Research Department, 2003)
This study compares the forecasting performance of a structural exchange rate model that combines the purchasing power parity condition with the interest rate differential in the long run, with some alternative models. The analysis is applied to the Norwegian exchange rate. The long run equilibrium relationship is embedded in a parsimonious representation for the exchange rate. The structural exchange rate representation is stable over the sample and outperforms a random walk in an out-of-sample forecasting exercise at one to four horizons. Ignoring the interest rate differential in the long run, however, the structural model no longer outperforms a random walk.
Keywords: C22; C32; C53; F31; 330; Equilibrium real exchange rate; cointegration VAR; out-of-sample forecasting